Judicial Discretion in Post-Divorce Child Custody Determinations Based on the Best Interests of the Child Principle: A Perspective of the Compilation of Islamic Law (KHI) - Muhammad Fazrianur Arridho; Kania Arbella (Mitsaqan Ghalizan, 2026)
Divorce in modern society gives rise to various complex legal implications, particularly regarding the protection, rights, and well-being of children. In Islamic family law, the concept of hadhanah, or the right of custody, occupies a central position. This study aims to analyse positive law and Islamic law texts regarding the existence of hadith and to evaluate the consistency of its application in Religious Courts to ensure legal certainty oriented toward child protection. The research method used is normative legal analysis, with a descriptive-analytical approach, based on library research. The results of the study indicate that although Article 105 of the Compilation of Islamic Law (KHI) grants the mother priority in the custody of a minor child (mumayyiz), in practice, judges in Religious Courts do not rigidly apply this rule. Judges exercise legal ijtihad and legal discovery by prioritising the child’s best interests. Judges’ considerations are multidimensional; therefore, hadhanah is viewed as a manifestation of parents’ fundamental responsibility. Consequently, rulings by judges within the Religious Court system place greater emphasis on the party best able to ensure the child’s holistic well-being and development rather than merely adhering to the literal text of the law.